AGILE GOVERNANCE IN THE SELF-ASSESSMENT TAX REPORTING APPLICATION (E-SATRIA) FOR LAND AND BUILDING TAX AND THE DUTY ON THE ACQUISITION OF LAND AND BUILDING RIGHTS AT THE REGIONAL REVENUE MANAGEMENT AGENCY (BPPD) OF BANDUNG CITY - Muhamad Bangun Nagari; Panji Santosa; Tati Sarihati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research is aimed at understanding the practice of Agile Governance in public service, specifically in the E-Satria service (Electronic Self-Assessment Tax Reporting App). Before E-Satria was launched, in 2017 the West Java Provincial Government was recognized by the central government for its technological excellence. Based on preliminary observations, several facts were found in the field regarding E-Satria: E-Satria has produced positive outcomes in transforming tax reporting services, and BPPD (Regional Revenue Management Agency) has been able to provide services that recognize current societal needs and developments, responding to them effectively. Agile Governance is used in this research as an analytical model capable of assessing the agility of government service programs, especially those based on digital services. This model has six characteristics:1. Good Enough Governance. 2.Business Driven. 3.Human Focused, 4. Based on Quick Wins. 5.Systematic and Adaptive Approach. 6.Simple Design and Continuous Refinement. The research uses a qualitative method, with in-depth interviews, observation, and document studies as the data collection techniques. The research findings indicate that BPPD Bandung City has demonstrated agile characteristics in implementing E-Satria. More specifically, BPPD has shown all six characteristic Good Enough Governance: The system development meets the needs of the public in regional tax service delivery. Business Driven: There is an increase in service effectiveness and efficiency. Human Focused: All employees are involved in contributing ideas for service improvement. Based on Quick Wins: The early success of the innovative E-Satria application has become a motivator for continuing governance initiatives. Systematic and Adaptive Approach: BPPD is capable of adapting to new environmental developments as they arise. Simple Design and Continuous Refinement: BPPD adopts simple designs and continuously improves its service development.